Impact of Incretin Hormone Receptors on Insulin-Independent Glucose Disposal in Model Experiments in Mice - Ovlund, Tina; Pacini, Giovanni; Ahrén, Bo (Frontiers in Endocrinology, 2021)
A large contribution to glucose elimination from the circulation is achieved by insulin-independent processes. We have previously shown that the two incretin hormones, glucose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide-1 (GLP-1) increase this process and, therefore, seem to contribute to glucose disposal both through this effect and through the classical incretin effect resulting in enhanced insulin levels. We have now explored in more detail the potential contribution by incretin hormone receptors to insulin-independent processes for glucose elimination. To that end, we have performed intravenous glucose tests (0.35g/kg) in C57BL/6J mice and analyzed glucose elimination rate and glucose effectiveness (i.e., insulin-independent glucose disposal, SG) in wildtype mice and in mice with genetic deletion of GIP receptors or GLP-1 receptors. We performed studies with or without complete blockade of insulin secretion by the drug diazoxide (25 mg/kg). The mice were anesthetized with a novel fentanyl citrate/fluanisone formulation, called Fluafent, together with midazolam. Initially we demonstrated that glucose and insulin data after intravenous and oral glucose were not different using this anesthesia compared to the previously commonly used combination of HypnormR and midazolam. The results show that SG was reduced in GLP-1 receptor knockout mice, whereas there was no difference between GIP receptor knockout mice and wildtype mice, and this was evident both under normal conditions and after complete inhibition of insulin secretion. The study therefore indicates that insulin-independent glucose elimination requires active GLP-1 receptors and thus that the two incretin hormone receptor types show dissociated relevance for this process.